Access and use of ICT for self-care purposes by type 2 diabetes patients - Díaz de León-Castañeda, Christian (Horizonte Sanitario, 2025)
Objective: To explore the access and use of Information and Communication Technologies (ICT) for self-care purposes in patients with type 2 diabetes (T2D) users of public health services in Mexico. Materials and Methods: A case study design with a mixed approach was used. Semi-structured interviews and a structured questionnaire were applied to 15 patients with T2D who formed a mutual aid group (MAG) in a primary care health clinic of the Institute of Social Security and Services for State Workers (ISSSTE) in the city of Morelia, Michoacán, Mexico. The interviews were audio-recorded, transcribed and analyzed in Atlas Ti software. The responses to the questionnaire were captured and analyzed in SPSS statistical software. Results: In the quantitative approach, a higher proportion of patients with access and use of ICTs such as smartphones (86.7%) compared to computers (33.3%) was identified. Through the qualitative approach, difficulties in developing digital skills for computer use were identified. However, it was found that patients have developed these skills for the use of the smartphone for general purposes and for self-care of their health. The adoption and use of applications (App) or web portals that can help in their self-care are identified as opportunities for patients. The development of their own systems and/or digital tools aimed at patients and the implementation of strategies for access and effective use of ICT by patients are opportunities for health institutions. Conclusion: Access to and use of ICT by patients favors the promotion of health and self-care of patients with T2D who use public health services. Keywords: Type 2 diabetes; Information technology; eHealth Strategies; Self care; Health promotion.